Hawaiʻi place names : shores, beaches, and surf sites - Clark, John R. K., 1946- (Book collections on Project MUSE., 2002)
In his latest book, John Clark, author of the highly regarded "Beaches of Hawaii" series, gives us the many captivating stories behind the hundreds of Hawaii place names associated with the ocean--the names of shores, beaches, and other sites where people fish, swim, dive, surf, and paddle. Significant features and landmarks on or near shores, such as fishponds, monuments, shrines, reefs, and small islands, are also included. The names of surfing sites are the most numerous and among the most colorful: from the purely descriptive (Black Rock, Blue Hole) to the humorous (No Can Tell, Pray for Sex). Clark began gathering information for the "Beaches" series in 1972, and during the years that followed interviewed hundreds of informants, many of them native Hawaiians, and consulted dozens of Hawaiian reference books, newspapers, and maps. A significant amount of the oral history he collected was unrecorded and remained only in his notebooks and memory. Hawaii Place Names: Shores, Beaches, and Surf Sites is the final result of those years of research, and like its popular predecessors, it benefits substantially from Clark's having spent a lifetime surfing and swimming Hawaii's beaches. Presented in the same convenient format as Pukui, Elbert, and Mookini's Place Names of Hawaii (UH Press, 1974) this rich compendium of information on Hawaii's surf, shore, and beach sites will satisfy visitors and residents alike